HUMAN SPIRITUALITY: COMPLEX STRUCTURE (SYNERGETIC APPROACH) (Conferencea, 2024)
The article examines the complex and mysterious nature of a person’s inner world, his spirituality. The author emphasizes that the study of this world raises many questions and conflicting conclusions. Based on the works of scientists, the article emphasizes the uniqueness of human spiritual properties and the importance of studying them for the development of society. In the context of the synergetic concept, the article offers definitions of man and his world, and also emphasizes the need for self-education and self-development for successful activities in the constantly changing conditions of society.